Un défi pour La Réunion : une dynamique périurbaine mieux maîtrisée - Joël Ninon (Projets de Paysage)
Urban development in Reunion really took off with the departmentalization of the island in 1946. The developments that accompanied this change of status were meant to catch up with delays in all areas. From the 1980s, the combined demographic pressure induced by an unfinished socio-economic and infrastructural development has been characterized by an unprecedented urban sprawl. The stakes are high for an island with limited space and in which agricultural surface is not extensible, and to which sugar cane remains a major source of export. This article outlines the process and the spatial indications of the "generalized" phenomenon of peri-urbanization. In addition to the spatial consequences of the phenomenon, and in view of the island’s sustainable development, it also addresses the chosen options towards a better control of urban sprawl in Reunion.